Організаційно-правові засади попередження злочинності неповнолітніх осіб (на матеріалах українських губерній у складі Російської імперії) - Стороженко, І. О.; Storozhenko, I. O. (Юридична наука. - 2020. - № 2 (104). - С. 519-526, 2020)
Досліджено організаційно-правові засади попередження злочинності неповнолітніх осіб на матеріалах українських губерній, які знаходились у складі Російської імперії у їх історико-правовому осяганні. Доведено, що започатковувана на початку XX століття система дитячих судів, по суті, стала першою повноцінною спробою втілення принципу гуманізму по відношенню до неповнолітніх злочинців. Одночасно з реалізацією в кінці XIX - початку XX століття прогресивних заходів, що відповідають духу часу і фактичному стану злочинності неповнолітніх, розкрилися вельми істотні проблеми і протиріччя нового підходу до регулювання правового становища криміналізованих дітей і підлітків.

The relevance of the article is that in almost every country the problem of crime is relevant, and of particular concern is the fact that a fairly large percentage of criminals are minors. A characteristic feature of recent years is also a change in the structure of juvenile delinquency, in particular due to the predominance of mercenary and violent crimes. The number of aggressively-minded informal youth associations is growing, and there are other negative modifications of youth consciousness with a predominance of selfish orientation. This state of affairs has led to a certain intensification of state bodies in the field of juvenile delinquency prevention, but unfortunately, the outlined measures do not give the expected results: released from prisons, a significant number of juveniles re-enter the criminal path. The scientific article devoted to the study of the organizational and legal foundations for the prevention of crime of minors on the materials of the Ukrainian provinces, which were part of the Russian Empire in their historical and legal understanding. According to the results of the study, it was proved that the system of children’s courts, begun at the beginning of the 20th century, in fact, was the first full-fledged attempt to implement the principle of humanism in relation to juvenile criminals. At the same time, it should not be overlooked that, simultaneously with the implementation in the seconds part of XIX – first part XX centuries of progressive measures consistent with the spirit of the times and the actual state of juvenile crime, very significant problems and contradictions of the new approach to regulating the legal situation of criminalized children and adolescents were revealed. The possibility of applying a special – educational approach to juvenile offenders was seriously limited by the lack of actually established institutions for the maintenance of children and adolescents. In this case, the success of the implementation of certain legal regulation measures directly depended on the material base, and therefore, their result and success were nullified. Attention was drawn to the fact that the actual establishment of special procedures for the administration of juvenile justice and the establishment of specialized courts had necessitated the almost universal introduction of special facilities for convicts and juveniles detained during pretrial investigations and trials. It has been proved that the tasks of the court included not only the fight against juvenile delinquency, but also the adoption of measures for street children, as well as the protection of the interests of children, that is, by their activities, the peculiarities of the proceedings, the courts ensured the prevention of juvenile delinquency, influencing its causes.

Исследованы организационно-правовые основы предупреждения преступности несовершеннолетних лиц на материалах украинских губерний, которые находились в составе Российской империи в их историко-правовом постижении. Доказано, что начинающаяся в начале XX века система детских судов, по сути, стала первой полноценной попыткой воплощения принципа гуманизма по отношению к несовершеннолетним преступникам. Одновременно с реализацией в конце XIX – начале XX века прогрессивных мер, соответствующих духу времени и фактическому состоянию преступности несовершеннолетних, раскрылись весьма существенные проблемы и противоречия нового подхода к регулированию правового положения криминализированных детей и подростков.
Organizational and legal principles of prevention of junior crime (on the materials of Ukrainian provinces in the Russian Empire)
Стороженко, І. О. Організаційно-правові засади попередження злочинності неповнолітніх осіб (на матеріалах українських губерній у складі Російської імперії) / Стороженко І. О. // Юридична наука. - 2020. - № 2 (104). - С. 519-526. - DOI: https://doi.org/10.32844/2222-5374-2020-104-2.58.
Стороженко, І. О. (2020). ОРГАНІЗАЦІЙНО-ПРАВОВІ ЗАСАДИ ПОПЕРЕДЖЕННЯ ЗЛОЧИННОСТІ НЕПОВНОЛІТНІХ ОСІБ (НА МАТЕРІАЛАХ УКРАЇНСЬКИХ ГУБЕРНІЙ У СКЛАДІ РОСІЙСЬКОЇ ІМПЕРІЇ). Юридична наука, (2(104), 519–526. https://doi.org/10.32844/2222-5374-2020-104-2.58.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Україна. Ukraine. Украина; Кримінологія. Criminology. Криминология; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; неповнолітні; minors; несовершеннолетние; українські губернії; Ukrainian provinces; украинские губернии; організаційно-правові засади; organizational and legal principles; организационно-правовые основы; неповнолітні злочинці; juvenile criminals; несовершеннолетние преступники; протидія злочинності; crime prevention; противодействие преступности